5. Accelerated Fracture Healing Targeting Periosteal Cells: Possibility of Combined Therapy of Low-Intensity Pulsed Ultrasound (LIPUS), Bone Graft, and Growth Factor (bFGF). Issue 8 (August 2016) - Uchida, Kentaro; Urabe, Ken; Naruse, Koji; Mikuni-Takagaki, Yuko; Inoue, Gen; Takaso, Masashi
Abstract : We have studied the mechanism of fracture healing, and the effect of LIPUS, bone graft and growth factor on accelerating fracture healing. We present here the results of our research. To examine callus formation cells in fracture healing, we made marrow GFP chimera mice and a fracture model of marrow mesenchymal stem cell GFP chimera mice. It was demonstrated that periosteal cells were essential for callus formation. We focused on periosteal cells and examined the effect of LIPUS. In an in vitro experiment using a cultured part of the femur, LIPUS promoted ossification of the periosteal tissue. Further, LIPUS accelerated VEGF expression in the experiment using the femoral fracture model of mice. From these results, it was suggested that activation of periosteal cells might play a role in the fracture healing mechanism of LIPUS. Next, we discussed the possibility of combined therapy of LIPUS, bone graft and growth factor. Therapy involving the topical administration of bFGF using a controlled release system and bone graft could promote callus formation. In addition, LIPUS was able to promote membranaceous ossification after the bone graft. It was suggested that combined therapy of LIPUS, bone graft and bFGF could be a new option for treating fractures.